STUDY ON IN-PLANE STABILITY OF THE WTZ350 GEOPHYSICAL RIG’S MAST - ZHANG JiaJia; JIANG FaGuang; YANG FengSHen; YANG MaoJun; ZHAN Jin (Jixie qiangdu)
In-plane stability calculation model of mast was set up firstly based on the thin-walled components flexuraltorsional theory. Theoretical arithmetic,according to the energy method and principle of stationary potential energy,and numerical simulation and verification of the derrick’s in-plane stability were conducted,and the results of theoretical calculation and numerical simulation basically tallied. Then,material nonlinear analysis was conducted on 5 kinds of structural steel masts.Results show that: maximum stress of the thin-walled derrick exceeds the yield strength of the material when linear buckling occurs in the lifting drilling process for the 5 kinds of structural steel masts and the type of instability is elastic-plastic buckling;The elastic-plastic buckling safety factor y becomes larger with the increasing of yield strength of materials,and the linear fitting function is y = 0. 00707x- 0. 01651; The steel materials that whose yield strength is greater than 313. 5 MPa meet the requirements of derrick’s in-plane elastic-plastic stability.